The effects of uncontrolled deforestation and development to Malaysia’s ecosystem / Balqis Jasni, Ponirin Amin and Rafeah Legino - Jasni, Balqis; Amin, Ponirin; Legino, Rafeah (Research Innovation Business Unit, 2014)
Tropical deforestation in Malaysia is occurring at an alarming rate, which is treating the ecological integrity of protected areas. According to the writer of the Star newspaper, Tashny Sukumaran (2013), Malaysia saw 115% increase in deforestation during the first months of 2013. This fact was taken from a forest tracking tool developed by National Aeronautics and Space Administration (NASA) researchers. Therefore, the objective of this study is to gather evidence about deforestation that affects Malaysia’s ecosystems, in order to produced installation artwork. Data collection, data categorization was done based on certain methods suggested by J.J Winckelmann(1764) as a main part. The methodology of Feldman’s theory was used in the study of artworks of my artist references. This process helps me think critically because it involves Feldman’s model of description, analysis, interpretation and judgement. According to Wikipedia, installation art describes an artistic genre of three-dimensional works that are often site-specific and designed to transform the perception of a space. Through installation, the simulation of two thousand Morpha Helena butterflies that produced rhythmic movement and fantasized version in accordance within the content and context. The uses of butterflies as main and major subject matter is inspired through the adaptation of other artists (Paul Villinski, Ryan McJunkin, Carolyn Wong, William Du, Rosemary Burden and Taegan Roberts) and collaborate with the sense of environment sensitivity. According to Telegraph (2012), butterflies are more endangered than tiger. Bumblebees, beetles and butterflies are at greater risk of extinction than lions and tigers; this is referring to a global study by Zoological Society of London. All species of insects, butterflies and invertebrates are in danger from further habitat loss caused by climate changes. Printmaking has a very wide definition and different perspective depends on how someone interprets the definition of printmaking itself. According to Michel Melot (1998), he defines the term ‘print’, which conveys the idea of impressing a design or image, of transferring it from one surface to another surface. This is why I chose installation technique rather than conventional print making techniques because installation using silk screen butterflies is considered as printmaking and I believed this installation can attract attention. Here people can touch, feel and internalise the artwork rather than watching it inside a frame. My product’s size is 30 feet in length and 16 feet in height. Through the representational elements, the artwork is formed to convey the idea, in how this kind of insects is culturally a popular motif. This is because of this wildlife visual and rarely seen in our surroundings because of climate changes. This study and project will be a reference to the next generation to extend their knowledge about the cause and effects of uncontrolled deforestation and development to our country. This product can be commercialised anywhere such as inside of shopping mall, library, community park and many other places to be seen b communities so that the massage can spread successfully and influence the audiences thinking to take the preventative action.